ANALISIS KETERLIBATAN ORANG TUA TERHADAP KEDISIPLINAN BELAJAR SISWA KELAS 2 SEKOLAH DASAR - Laily Nurmalia; Melly Admelia; Nabila Farhana; Koyimah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to analyze the involvement of parents in the learning discipline of grade 2 elementary school students. This study used a qualitative method with a case study approach. Based on the results of research and data analysis obtained from observations and interviews with class teachers, parents, and students, it was concluded that some students still lacked discipline in learning, especially in the aspect of collecting assignments. This was due to the busy work experienced by the parents of these students, which caused a lack of parents’ involvement in accompanying children to study. As a result, students were often late in collecting assignments that the teacher gave. The participation of parents in the child's learning process meant to involve themselves in helping and assisting children in doing school assignments. Elementary school-age children still needed assistance from others, especially from parents, in carrying out the learning process to support the success of the child's education process, especially in child behavior development. One aspect of children’s behavior development that needed to be considered was discipline. One of the aspects of students’ learning discipline was collecting assignments based on the time determined by the teacher and is responsible for doing the tasks given by the teacher. Learning discipline had several factors, one of which was external factors coming from the family environment.